If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 1.5 = 7 Reorder the terms: 1.5 + 5p = 7 Solving 1.5 + 5p = 7 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + 5p = 7 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + 5p = 7 + -1.5 5p = 7 + -1.5 Combine like terms: 7 + -1.5 = 5.5 5p = 5.5 Divide each side by '5'. p = 1.1 Simplifying p = 1.1
| 3(4b+12c+12c)=x | | 9p+5.8=4 | | -9-12+-5= | | 5/2b=27.5 | | -1-5x=2x-71 | | 3(4b+12c+11)= | | 3(y+4)=4(y+5) | | 18+6B=-72 | | 5p+1=2.2 | | 6y-4=2x-8 | | (6x+8)+(-7x-11)= | | 4p+3=.8 | | 4(4/5)+4(-9/5)=-4 | | (x+4)/(4)=(x)/(x-2) | | 9-12+5= | | cx-y=2 | | (x-3)-9=0 | | 9p+5.8= | | 4(4/5)-(-9/5)=5 | | 7x+9y-6x-11y= | | 60x-60x^3=0 | | 9p+4=5.8 | | 9--12+5= | | 2x-((3x^2)/36) | | 9/4y=2/3y | | 5y+2=4.5 | | -7+2x-5x=-7 | | y=4(4/5)-5 | | 6-3(x+2)=12 | | -6a-a= | | 2k+3=5.4 | | 36t^2/3+36t^1/3+9=0 |